Causes and Timing of Unplanned 90-day Readmissions Following Spine Surgery. Issue 14 (15th July 2018) - Hills, Jeffrey; Sivaganesan, Ahilan; Khan, Inamullah; Chotai, Silky; Weisenthal, Benjamin; Freeman, Thomas; Butler, Marjorie; Wick, Joseph; Daryoush, Joshua; Asher, Anthony; Devin, Clinton J.
Abstract : Study Design: Retrospective cohort study. Objective: The aim of this study was to evaluate the causes, timing, and factors associated with unplanned 90-day readmissions following elective spine surgery. Summary of Background Data: Unplanned readmissions after spine surgery are costly and an important determinant of the value of care. Several studies using database information have reported on rates and causes of readmission. However, these often lack the clinical detail and actionable data necessary to guide early postdischarge interventions. Methods: Patients undergoing elective spine surgery for degenerative disease at a major medical center were enrolled in a prospective longitudinal registry. Patient and surgery-specific characteristics, baseline, and 3-month patient-reported outcomes were prospectively recorded. Readmissions were reviewed retrospectively to establish the reason and time to readmission. A multivariable Cox proportional hazard model was created to analyze the independent effects of several factors on readmission. Results: Of 2761 patients with complete 3-month follow-up, 156 had unplanned 90-day readmissions (5.6%). The most common reason was surgery-related (52%), followed by medical complications (38%) and pain (10%). Pain readmissions presented with a median time of 6 days. Medical readmissions presented at 12 days. Surgical complications presented at various times with wound complications at 6 days, cerebrospinal fluid leaks at 12 days, surgical site infections at 23 days, and surgical failure at 38 days. A history of myocardial infarction, osteoporosis, higher baseline leg and arm pain scores, longer operative duration, and lumbar surgery were associated with readmission. Conclusion: Nearly half of all unplanned 90-day readmissions were because of pain and medical complications and occurred with a median time of 6 and 12 days, respectively. The remaining 52% of readmissions were directly related to surgery and occurred at various times depending on the specific reason. This timeline for pain and medical readmissions represents an opportunity for targeted postdischarge interventions to prevent unplanned readmissions following spine surgery. Level of Evidence: 3